Kaligrafi islam sebagai identitas kolektif dan gerakan sosial berbasis komunitas - Alif Fadilah; Nabila Nur Jihan; Muhammad Syahril; Muhammad Chaldun; Dadang Kuswana (Dimensia: Jurnal Kajian Sosiologi, 2026)
This study addresses the question of how Islamic calligraphy functions as a community-based social movement in an urban village context. The research employs a qualitative case study approach, collecting data through interviews, non-participant observation, and document analysis. Findings indicate that the calligraphy movement in the Kampung KB Wisata Budaya and Kaligrafi Jibja is semi-organic, originating from a bottom-up initiative by two key figures and accelerated through top-down support from the Kampung KB program. The movement not only reinforces local cultural identity but also presents a sustainable model for community empowerment. The study emphasizes the significance of leveraging religious and cultural symbols in strengthening social movements at the village level and offers practical insights for formulating community-participation-based policies.